Profil Guru Pembelajar Di Indonesia Dalam Merespon Tantangan Pendidikan Era Revolusi Industri 4.0 - Prastowo, Andi (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
All sectors of community life in Indonesia, including the education sector, have been impacted by the change from the transition of the 3rd Industrial Revolution era to the 4th Industrial Revolution (4IR) era, from the 20th to the 21st century. These changes have changed the paradigms, challenges and needs of teachers. However, the teacher profile that is in line with the educational needs of the 4IR Era is still being debated by academics today. This article examines the profile of teacher teachers in Indonesia in response to the needs of the 4IR era. This study uses a structured literature review research method. The findings from the study revealed that the profile of teacher-learners in Indonesia that is relevant to the challenges and needs of the 4IR Era are teachers should have a growth mindset, continue to learn and develop themselves while inspiring others to do the same. They are also having educational skills, personal skills, social skills, and professional, as well as digital skills.